Peningkatan Kompetensi Keadaan Alam Indonesia Dengan Model Inquiry Based Learning Pendekatan Saintifik Pada Peserta Didik Kelas VII C SMP Negeri 2 Kota Pekalongan (Universitas Negeri Semarang, 2016)
This research aims to improve the competence of Indonesian natural state by applying a model of Inquiry Based Learning scientific approach. This research uses classroom action research. The action in this research there are two cycles, with each cycle there are four stages. Learning to use a model of inquiry based learning approach to learning science scientifik social competence of the state of Indonesia's natural learning process centered on the learner, the teacher's role as facilitator in the learning. The evaluation from the first cycle result average value of learners with a mastery level of 8.33%. Cycle II with an average value of 100% mastery level. The significant improvement of the learning process competencies natural state of Indonesia using models Inquiru Based Learning Approach Scientifik learner class VIIC SMPN 2 Pekalongan City in the academic year 2015/2016. Activities learners during the learning process also has increased. Penelitian ini bertujuan untuk meningkatkan kompetensi keadaan alam Indonesia dengan menerapkan model Inquiry Based Learning pendekatan scientific. Penelitian ini menggunakan PTK. Tindakan dalam peneltian ini terdapat dua siklus, dengan masing-masing siklus empat tahap. Pembelajaran dengan menggunakan model inquiry based learning pendekatan scientifik pada pembelajaran IPS tentang kompetensi keadaan alam Indonesia, proses pembelajaran berpusat kepada peserta didik, guru sebagai fasilitator dalam pembelajaran. Hasil evaluasi dari siklus I diperoleh hasil nilai rata-rata peserta didik dengan tingkat ketuntasan sebesar 8.33%. Siklus II dengan nilai rata-rata tingkat ketuntasan 100%. Diketahui adanya peningkatan yang cukup signifikan dari proses pembelajaran kompetensi keadaan alam Indonesia dengan menggunakan model Inquiri Based Learning Pendekatan Scientifik pada peserta didik kelas VIIC SMPN 2 Kota Pekalongan tahun pelajaran 2015/2016. Aktivitas peserta didik saat proses pembelajaran juga mengalami peningkatan yang signifikan.